Development of the barriers to opioid access scale among individuals with chronic pain - Sujith Ramachandran; Stefan Kertesz; Emily Gravlee; Prachi Prajapati; John P. Bentley; Yi Yang (Exploratory Research in Clinical and Social Pharmacy)
Background: Measurement of accessibility is a crucial pillar in assessing equity of access to pain treatment, particularly in the context of reducing opioid prescribing in response to rising overdose deaths in the United States. Objectives: The aim of this study was to develop an instrument to measure barriers to prescription opioid access among individuals with chronic pain and test its psychometric properties. Methods: This study used a cross-sectional online survey of a convenience sample of adults (>18 years) who reported any type of pain for at least 45 days or more in the previous 3 months. The survey captured demographic characteristics, self-reported medication use characteristics, and measures such as the Brief Pain Inventory-Short Form and the PROMIS Global Health measure, along with an item pool of potential questions that measure barriers to opioid access. Results: Respondents (N = 200) were 89 % women, 86 % White, averaging 45.32 years old (SD:11.79), and reported poor quality life. Two subscales, Access to Care and Patient Concerns, were identified for the Barriers to Opioid Access Scale with good internal consistency reliability (α = 0.909 and 0.835, respectively). In multivariable analyses, the Access to Care subscale was associated with the PROMIS mental health score (−2.44; 95 % CI: −3.77, −1.11), and the Patient Concerns subscale was associated with self-reported frequency of opioid use (−0.70; 95 % CI: −0.99, −0.40). Conclusions: The newly developed BOAS has the potential to serve as a tool for capturing quality of pain treatment as well as measuring the impact of policy changes on the quality of treatment provided to patients with chronic pain.